Training on processing Buleleng local wine into sustainable culinary tourism products in Banjar Village, Buleleng - Putu Eka Wirawan; I Made Sudjana; A.A. Ayu Arun Suwi Arianty; I Gusti Suka Arnawa; Komang Ratih Tunjungsari (Community Empowerment, 2021)
Banjar Village, Banjar District, Buleleng Regency is known as a center for horticultural commodities in the form of fruits, one of which is grapes. The purpose of this service is to improve the ability and basic development skills in processing local wines that have existed previously so that they have new innovations and creativity. The method used to overcome the problem is done by using the method of knowledge and skill transfer to a group of wine farmers in Banjar Village. As a result of this community service, the wine farmer group has deeper insight and is more creative and innovative in processing local Buleleng grapes into sustainable culinary tourism products, such as wine, peanut brittle, and herbal tea.